2016
DOI: 10.1186/s12864-016-2594-5
|View full text |Cite
|
Sign up to set email alerts
|

GWAS and transcriptional analysis prioritize ITPR1 and CNTN4 for a serum uric acid 3p26 QTL in Mexican Americans

Abstract: Background: The variation in serum uric acid concentrations is under significant genetic influence. Elevated SUA concentrations have been linked to increased risk for gout, kidney stones, chronic kidney disease, and cardiovascular disease whereas reduced serum uric acid concentrations have been linked to multiple sclerosis, Parkinson's disease and Alzheimer's disease. Previously, we identified a novel locus on chromosome 3p26 affecting serum uric acid concentrations in Mexican Americans from San Antonio Family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…The final result would be a significant decrease in uric acid circulating level. In contrast to these results, On the other hand, several studies agree with our results favoring the view that reduced uric acid in MS is secondary to its peroxynitrite scavenging activity during inflammatory disease activity, rather than a primary deficiency [16,37,38]. Also, in this study it was found that urinary uric acid level was lower in SPMS than RRMS and inversely correlated with disability score (EDSS and number of relapses) which agree with Markowitz et al [39] who found that inosine treatment (precursor of uric acid) increased serum uric acid levels and was associated with a significant decrease in the number of gadolinium enhanced lesions and improved EDSS.…”
Section: Discussionsupporting
confidence: 77%
“…The final result would be a significant decrease in uric acid circulating level. In contrast to these results, On the other hand, several studies agree with our results favoring the view that reduced uric acid in MS is secondary to its peroxynitrite scavenging activity during inflammatory disease activity, rather than a primary deficiency [16,37,38]. Also, in this study it was found that urinary uric acid level was lower in SPMS than RRMS and inversely correlated with disability score (EDSS and number of relapses) which agree with Markowitz et al [39] who found that inosine treatment (precursor of uric acid) increased serum uric acid levels and was associated with a significant decrease in the number of gadolinium enhanced lesions and improved EDSS.…”
Section: Discussionsupporting
confidence: 77%
“…40 Furthermore, genetic variants in CNTN4 are associated with elevated serum uric acid, thromboxane A2 formation and with an excess of cardiovascular events. 41,42 Our results showed that rs60314379, located in GRK4, was asso- has been associated with genetic and acquired hypertension. [43][44][45] Differential functional expression of GRK family proteins in human myocardial tissues has shown that, although GRK2, GRK3, and GRK5 expression is abundant, GRK4, GRK6 and GRK7 transcripts are only scarcely detectable in the healthy human heart.…”
Section: Cumulative Effects Of the 35 Genetic Variants On Cardiovasmentioning
confidence: 59%
“…Mutations in CNTN4 in humans are associated with 3p deletion syndrome and autism spectrum disorders 40 . Furthermore, genetic variants in CNTN4 are associated with elevated serum uric acid, thromboxane A2 formation and with an excess of cardiovascular events 41,42 …”
Section: Discussionmentioning
confidence: 99%
“…Solute carrier family 22 member 1 exhibited the strongest interaction with ABCG2, which is expressed in the kidney and mediates the transport of xenobiotics, endogenous organic anions and urate (43). PRKG2 exhibited the strongest interaction with inositol 1,4,5-trisphosphate receptor type 1, which was previously reported to be associated with high serum uric acid concentrations (44). In the next step, all 79 candidate genes in the PPI network were used in the BP with ClueGO plugin.…”
Section: Functional Analysis Of the Co-expression And Ppi Networkmentioning
confidence: 99%